Analisis Hukum Islam Dalam Penerapan Bagi Hasil Pada Bank Muamalat Sukabumi - Nela, Nela Nurlaelasari (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2022)
This study aims to find out how the murabahah contract compares with the musyarakah mutanaqisah contract at bank Muamalat Indonesia Sukabumi Branch according to Islamic law. The method in this study uses a qualitative method with a descriptive approach where this research is to explain the problem in depth. And the data used by this study are primary data through observation, interviews, and documentation. Tempat research at Bank Muamalat Indonesia Sukabumi Branch. Based on the results of the study showing that Bank Muamalat Indonesia Sukabumi Branch carries out its business activities based on sharia principles, Bank Muamalat in the financing products carried out, gives freedom to its customers to choose what contract to use in a financing, be it a murabahah contract or a musyarakah contract in accordance with the specifications of working capital needs for purchasing business assets. The comparison between Sharia mortgages and conventional mortgages is from the agreement, Sharia mortgages can be carried out on several alternative contract options comparable to customer needs, including KPR IB Jual Beli (murabahah scheme) and KPR IB Ownership in stages (musyarakah mutanaqisah). Meanwhile, mortgage contracts are based on certain interest rates, the form of which can fluctuate. Sharia mortgages do not recognize interest but use approved home sales prices, plus profits for banks that range from 15-20% per year. Then, thecomparison of the Murabahah Contract and the Musyarakah Mutanaqisa h Agreementon the Muamalat iB Mortgage Financing with the Murabahah contract consists of only one contract, namely the buying and selling contract (Ba'i), however, it is common to use the wakalah contract to facilitate the purchase process. So the bank made a wakalah agreement letter. Meanwhile, the Musyarakah Mutanaqisah contract consists of three contracts, namely the syirkah contract, the sale and purchase contract (Ba;i) and the ijarah (lease) contract. Keywords: islamic law, comparison of murabahah contract and musyarakah mutanaqisah contract